2007
DOI: 10.3327/jnst.44.657
|View full text |Cite
|
Sign up to set email alerts
|

Neutronics Experimental Study on Tritium Production in Solid Breeder Blanket Mockup with Neutron Reflector

Abstract: Neutronics experiments have been performed for the solid breeder blanket using a DT neutron source at the FNS facility in JAEA. We have applied the blanket mockup composed of two enriched Li 2 TiO 3 and three beryllium layers, and measured the detailed spatial distribution of the tritium production rate (TPR) using enriched Li 2 CO 3 pellets. TPRs in the pellets have been measured by a liquid scintillation counter. Experiments have been done under a condition with a neutron reflector surrounding the DT neutron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…At the Fusion Neutronics Source (FNS) facility of Japan Atomic Energy Agency (JAEA), a series of blanket neutronics experiments with DT neutrons simulating the WCCB TBM has been carried out for the verification of the prediction accuracy of neutronics performances [2][3][4]. It was demonstrated that the total integrated tritium production in the TBM is predictable within the accuracy of about 10% [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the Fusion Neutronics Source (FNS) facility of Japan Atomic Energy Agency (JAEA), a series of blanket neutronics experiments with DT neutrons simulating the WCCB TBM has been carried out for the verification of the prediction accuracy of neutronics performances [2][3][4]. It was demonstrated that the total integrated tritium production in the TBM is predictable within the accuracy of about 10% [3].…”
Section: Introductionmentioning
confidence: 98%
“…At the Fusion Neutronics Source (FNS) facility of Japan Atomic Energy Agency (JAEA), a series of blanket neutronics experiments with DT neutrons simulating the WCCB TBM has been carried out for the verification of the prediction accuracy of neutronics performances [2][3][4]. It was demonstrated that the total integrated tritium production in the TBM is predictable within the accuracy of about 10% [3]. However, an approximately 10% systematic overestimation of tritium production rate (TPR) was found only in the experiment with F82H, 6 Li-enriched Li 2 TiO 3 and beryllium when a neutron source reflector composed of type-316 stainless steel (SS316) was attached around the DT neutron source [2].…”
Section: Introductionmentioning
confidence: 99%